A 2008 Social Accounting Matrix for Mexico - Debowicz, Dario; Golan, Jennifer (International Food Policy Research Institute, 2012)
This Social Accounting Matrix (SAM) was built for the year 2008 for Mexico. It explicitly accounts for Oportunidades cash transfers. In this SAM, the government has a separate account for providing Oportunidades cash transfers to recipient households. The SAM has 14 different activities of production, 15 production factors, and 16 household groups. Using a cross-entropy technique,the SAM was balanced and made perfectly consistent with macro accounts of Mexico. This SAM was used to analyze the distributional effects of the Oportunidades conditional cash transfers in a top-down b ottom-up macro-micro simulation model that links in bi-directional and iterative way a computable general equilibrium (CGE) model and an econometrically informed micro simulation model.